Assessing the Efficacy of a School-Based Asthma Education Program for Children: A Pilot Study - Young, Nancy L. (Can J Public Health, 2001)
Background: Asthma diminishes the health-related quality of life for many school-aged children. This study sought to explore the effect of a School-Based Asthma Education Program (SBAEP) on quality of life. Methods: Children with asthma who attended grades 1 - 5 at two selected schools were requested to participate in this pilot study. Participants at one school were provided with a SBAEP, those at another school (control group) were provided with written educational material about asthma. The children completed the Paediatric Asthma Quality of Life Questionnaire (PAQLQ) before and one month after the educational interventions. Results: There were clinically important improvements in the SBAEP group in quality of life, specifically in the symptom subdomain. Conclusions: The “Air Force” SBAEP appears to result in a favourable trend in quality of life for children. A larger scale trial is required following revisions to the program.